Bach's testament: On the philosophical and theological background of the art of fugue - Göncz, Zoltan (Lanham Scarecrow Press, 2012)
Written late in his life, J. S. Bach s The Art of Fugue has long been admired in some quarters revered as one of his masterworks. Its last movement, Contrapunctus 14, went unfinished, and the enigma of its incompleteness still preoccupies scholars and musical conductors alike. In 1881, Gustav Nottebohm discovered that the three subjects of the movement could be supplemented by a fourth. In 1993, Zoltan Goncz revealed that Bach had planned the passage that would join the four subjects in an entirely unique way. This section has not survived, but, as Goncz notes, it must have been ready in the earliest phase of composition since Bach had created the expositions of the first three subjects from its disjointed parts. Goncz then boldly took on the task of reconstructing the original template by putting together the once separate pieces. In Bach s Testament: On the Philosophical and Theological Background of The Art of Fugue, Goncz probes the philosophic-theological background of The Art of Fugue, revealing the special structures that supported the 1993 reconstruction. Bach s Testament investigates the reconstruction s metaphysical dimensions, focusing on the quadruple fugue. As a summary of Zoltan Goncz s extensive research over many years, which resulted in the completion of the fugue, this work explores the complex combinatorial, philosophical and theological considerations that inform its structure. Bach s Testament is ideally suited not only to Bach scholars and musicologists but also intellectual historians with particular interests in 18th-century religious and philosophical ideas.